Regulators of inflammation and innate immunity identified in oesophageal cancer cell viability through implementation of a druggable genome siRNA library screen - Garry, Catherine E. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2015)
Inflammation initiated by gastroesophageal reflux disease (GORD) can lead to development of oesophageal adenocarcinoma (OAC), through a premalignant lesion, Barrett's oesophagus (BO). OAC has a 5-year survival of patients with localised OAC of 38%, which decreases dramatically if the tumour has spread. Due to the heterogeneity observed within cancers, identification of successful therapeutics has proved difficult. Small interfering RNAs (siRNA) may be targeted to induce gene silencing and subsequent loss of protein expression and function. Commercially available siRNA libraries enable simultaneous analysis of the effect of thousands of genes on a particular outcome. This study aimed to define therapeutic targets for OAC by utilising a siRNA library screening with the intention of identifying novel therapeutic targets for the treatment of OAC.
Keywords: Medicine, Ph.D.; Ph.D. Trinity College Dublin.